Proceedings 1st European Workshop on Usable Security 2016
DOI: 10.14722/eurousec.2016.23012
|View full text |Cite
|
Sign up to set email alerts
|

When SIGNAL hits the Fan: On the Usability and Security of State-of-the-Art Secure Mobile Messaging

Abstract: In this paper we analyze the security and usability of the state-of-the-art secure mobile messenger SIGNAL. In the first part of this paper we discuss the threat model current secure mobile messengers face. In the following, we conduct a user study to examine the usability of SIGNAL's security features. Specifically, our study assesses if users are able to detect and deter man-in-the-middle attacks on the SIGNAL protocol. Our results show that the majority of users failed to correctly compare keys with their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 9 publications
0
23
0
1
Order By: Relevance
“…High-risk users tend to be in areas where information security is important due to political instability, although wellknown activists and persecuted minorities in "stable" countries would count as high-risk users. Most usability studies over PGP, OTR, and Signal are still done with low-risk users such as college students, despite the use of secure messaging being considered to be important to high-risk users [22], [20], [19]. We would hypothesize that high-risk users have different threat models and so different requirements for privacy and secure messaging.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…High-risk users tend to be in areas where information security is important due to political instability, although wellknown activists and persecuted minorities in "stable" countries would count as high-risk users. Most usability studies over PGP, OTR, and Signal are still done with low-risk users such as college students, despite the use of secure messaging being considered to be important to high-risk users [22], [20], [19]. We would hypothesize that high-risk users have different threat models and so different requirements for privacy and secure messaging.…”
Section: Problem Statementmentioning
confidence: 99%
“…Encrypted messaging applications like WhatsApp, Telegram, and Signal are now the default encrypted messaging application for users that consider themselves to be high-risk. Usability studies have shown that although Signal (similar to OTR) is easy to setup and use, even highly-skilled users fail to use verification correctly [19]. Currently, the Signal Protocol is centralized, as a single server mediates the setup of the protocol in most widespread deployments (Signal, WhatsApp, Google Allo, Facebook Messenger, Wire).…”
Section: The Signal Protocol and Beyondmentioning
confidence: 99%
“…Developers do tend to verify keys, and it seems to be related to habits gained in software development. As shown by previous work, key verification is hard to both understand and use [6].…”
Section: Security Propertiesmentioning
confidence: 96%
“…A wellknown argument in favor of centralization and against standards was published by Moxie Marlinspike (Signal core developer) in his blog. 6 This blog-post, called "The eco-system is moving," has attracted considerable attention and is widely quoted by developers as a reason not to use standards, as centralization offers better control while federation can be "dangerous" in terms of security (D11), as it is hard to audit all the different implementations of the protocol and ensure correct updates. Developers from PGP, XMPP, and other protocols (Briar, Ricochet, etc.)…”
Section: Standardizationmentioning
confidence: 99%
“…However, it is not always the case that security breaches are due to technical problems, but may also be due to users' lack of security awareness. Schröder et al [24] presented a study on the Signal IM application and its end-to-end encryption, and showed that the majority of the tested users were not able to identify a MitM attack taking place on the application, even with alerts popping up. The users selected for the research were computer science students and, even with the expected security background, had their privacy exposed.…”
Section: Related Workmentioning
confidence: 99%